Knowledge management and early warning systems : the case of Southern African Development Community's conflict prevention strategy - Monama, Fankie Lucas (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Information Science))--Stellenbosch University, 2008.